2016
DOI: 10.1016/j.fgb.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of microsatellite markers for the oomyceta Aphanomyces euteiches

Abstract: Aphanomyces euteiches Drechsler is a serious pathogen of leguminous crops that causes devastating root rot of pea worldwide. Given that A. euteiches is a diploid organism, robust, codominant markers are needed for population genetics studies. We have developed and screened a microsatellite-enriched small-insert genomic library for identification of A. euteiches SSR containing sequences. Fourteen out of the 48 primer pairs designed to amplify SSR, produced unambiguous polymorphic products in our test population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A low level of genetic diversity in A. euteiches populations was observed between the different locations in France, as shown by the moderate number of multilocus genotypes identified (13 different MLGs within 205 isolates) including a predominant MLG (MLG1) shared by 54% of the isolates studied. This result is consistent with previous studies conducted on French and American A. euteiches populations, using codominant or dominant markers (Malvick and Percich, 1998 ; Wicker, 2001 ; Grünwald and Hoheisel, 2006 ; Mieuzet et al, 2016 ; Le May et al, 2018 ). In this study, the similar level of differentiation observed within and among populations also confirmed the absence of a clear genetic structure, as previously reported (Malvick and Percich, 1998 ; Wicker et al, 2001 ; Grünwald and Hoheisel, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A low level of genetic diversity in A. euteiches populations was observed between the different locations in France, as shown by the moderate number of multilocus genotypes identified (13 different MLGs within 205 isolates) including a predominant MLG (MLG1) shared by 54% of the isolates studied. This result is consistent with previous studies conducted on French and American A. euteiches populations, using codominant or dominant markers (Malvick and Percich, 1998 ; Wicker, 2001 ; Grünwald and Hoheisel, 2006 ; Mieuzet et al, 2016 ; Le May et al, 2018 ). In this study, the similar level of differentiation observed within and among populations also confirmed the absence of a clear genetic structure, as previously reported (Malvick and Percich, 1998 ; Wicker et al, 2001 ; Grünwald and Hoheisel, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
“…Twenty SSR primers, previously developed to amplify A. euteiches DNA (Mieuzet et al, 2016 ), were used in this study. The PCR reaction in simplex was carried out in 10 μL containing 1X Green GoTaq®Flexi Buffer, 2 mM MgCl2, 0.2 mM each dNTP (Promega, France), 1 μM each forward and reverse primer and 0.25 μM fluorescent-labeled M13 primer (FAM, Applied Biosystem), 1 U of GoTaq Flexi DNA polymerase (final concentration) (Promega, France) and 20 ng template DNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we confirm the pattern with an overall low level of genetic diversity found in previous studies of French and North American A . euteiches populations (Grünwald & Hoheisel, 2006; Le May et al, 2018; Malvick et al, 1998; Mieuzet et al, 2016; Quillévéré‐Hamard et al, 2018; Wicker et al, 2001). In the Grünwald and Hoheisel (2006) study, it was thought that a relatively higher diversity between populations was due to the limited spread of the soilborne pathogen.…”
Section: Discussionmentioning
confidence: 99%